Analisis Perbandingan Tribometer Types dengan Variasi Material - Review - Ramadhan, Adzan (Jurnal Rekayasa Mesin, 2015)
There are many tribometers especially friction test to make a research and to develop many kind of materials. Three types of tribometer that common to use for friction test are thrustwasher, block on ring, and pin on disk. In this study, Alumunium and Steel ST 40 was used to investigate the wearness value. The load used in the pin is 24,81 kg/mmÂ². The result showed that Aluminium have higher wearness value than Steel ST 40.